Associations between transactional sex and intimate and non-intimate partner violence: findings from project WINGS of Hope - Jiwatram-Negron, Tina (Journal of family violence, 2023)
Women who engage in transactional sex experience disproportionately high rates of intimate partner violence (IPV) and non-intimate partner violence (nIPV); However little research has examined whether these risks vary by recency of transactional sex. Drawing on baseline data from a GBV pilot intervention among 213 women with a history of substance use in Kyrgyzstan, we used descriptive, bivariate, and multivariate logistic regression analyses to examine the associations between history of transactional sex (never, former, recent-past 90 days) and IPV and nIPV. 108 (50.7%) participants reported a history of transactional sex: 65 of whom reported former transactional sex (FTS) and 43 of whom reported recent transactional sex (RTS). The prevalence of recent IPV (n = 163, 76.5%) and nIPV (n = 141, 66.2%) were high for the overall sample. Adjusted multivariate models indicated that women who reported RTS were significantly more likely to report recent physical, sexual, emotional, and any type of IPV, compared to women who reported FTS and no transactional sex (NTS). No significant differences were observed between women who reported NTS and FTS. Examining nIPV, women who reported RTS were significantly more likely to report deprivation of resources, injurious, physical, sexual, emotional, and any recent nIPV compared to women who reported FTS and NTS. Women who reported FTS were significantly more likely to report recent physical and sexual nIPV compared to women who reported NTS. Findings suggest that GBV risks shift over time with active engagement in transactional sex and by perpetrator, and that interventions should attune closely to these patterns.